Prostate cancer in young adults—Seventeen‐year clinical experience of a single center. Issue 1 (January 2017) - Huang, Tzu‐Hao; Kuo, Junne‐Yih; Huang, Yi‐Hsiu; Chung, Hsiao‐Jen; Huang, William J.S.; Wu, Howard H.H.; Chang, Yen‐Hwa; Lin, Alex T.L.; Chen, Kuang‐Kuo
Abstract : Background : In the general population, prostate adenocarcinoma affects predominately older men. If fact, most current guidelines suggest that males over the age of 50 years should undergo prostate cancer screening. However, the clinical behavior and prognosis of prostate cancer in young adults is not well defined. The aim of this study was to evaluate the clinical behavior, pathological characteristics, and prognosis of prostate cancer in young adults. Methods : We retrospectively reviewed the records of young patients (age, ≤50 years) in our hospital with prostate adenocarcinoma between 1997 and 2013. We compared data including initial presentation, cancer cell type, Gleason score, disease stage, prostate‐specific antigen (PSA) level, prostate volume, treatment, and survival between patients both younger and older than 50 years. Data were analyzed using the Kaplan–Meier method to assess survival. Results : Twenty‐six patients were enrolled in our study, accounting for 0.55% of all patients with a diagnosis of prostate cancer at our facility. All 26 patients had a pathology diagnosis of adenocarcinoma, with a mean age on diagnosis of 46.8 ± 2.8 years (range, 39–50 years). On initial presentation, patients older than 50 years more frequently displayed lower urinary tract symptoms (LUTS) than younger patients (62.3% vs. 30.4%, p = 0.008). There was no statistical difference in histological grade, disease stage, PSA level, overall survival, and biochemical‐free survival between the two groups. Conclusion : The result of our investigation indicated that prostate adenocarcinoma patients younger than 50 years had similar histological grade, disease stage, PSA level, overall survival, and biochemical‐free survival as the older population. However, patients younger than 50 years with prostate cancer less frequently showed initial symptoms of LUTS.